Effect of Light Spectra on Growth Performance and Immune Response of Koi Carp, Cyprinus carpio (Linnaeus, 1758) - Bairwa, Mukesh Kumar; Saharan, Neelam; Rawat, Kiran Dube; Tiwari, Virendra Kumar; Prasad, K. Pani (Fishery Technology, 2017)
The present study was undertaken to assess the growth performance and non-specific immune response of koi carp, Cyprinus carpio exposed to lightemitting diodes (LEDs): blue (450 nm), green (530 nm), yellow (530 nm) and red (630 nm) under long photoperiod (16 h light) for 90 days. White fluorescent light (simulated natural photoperiod, SNP) was used as control. Growth performance of fish was higher (p<0.05) in blue-LED and green-LED exposed groups with significantly higher weight gain percentage, FER and SGR and lower FCR. The concentrations of stress indicators: (cortisol and glucose) were significantly (p<0.05) higher in yellow-LED, red-LED and for control fish group. Total protein, globulin protein, lysozyme activity and respiratory burst activity was significantly higher (p<0.05) in blue-LED and green-LED exposed fish groups whereas, yellow-LED and red-LED exposed fish recorded decline in this parameters after 60 days. The present study recommends that blue and green lights are suitable for better growth and improving the non-specific immune system of koi carp.